Planejamento e controle na Polícia Militar do Pará: prática da racionalidade hierárquica - REIS, João Francisco Garcia (Universidade Federal do Pará, 2019)
This paper highlights the relations that occur within and at the Military Police of Pará; it aims to assess how planning, management and institutional control is performed; it describes and analyzes the relations between the strategic, tactical and operational levels. It identifies the codes of communication and how they are filtered and also analyzes the strategies of control; to achieve the objectives, it was used the heuristic method formed by two linear researches (both soldiers and officers) with scientific margins of errors and interviews, to verify the systemic relations in the institution and its surroundings, based on suppositions of Niklas Luhmann’s General Theory of social system, also using second order observation, employing theoretical definitions of communications, structural coupling and double contingency. The following hypothesis were tested and substantiated: Hypothesis 01: Management at the Military Police of the State of Pará - PMPA is extremely centralized, that is, organized under a bureaucratic logic and ruled by logics not exclusively technical or operational, being dominated by political logics. Hypothesis 02: Planning is not characterized according to demands, needs and internal technical and operational proposals of PMPA, corresponding to external political interests. Management planning is not ruled by technical aspects, but by predominant political aspects. This type of process, adding to beaurucratic centralization does not permit PMPA to effectively attend the demands that surge in their social environment (surrounding), being unable to control crime, new tactics of violence and new types of crime, etc. Hypothesis 03: In the organizational, strategic, tactical and operational plan surge dysfunctions that manifest in duplicity of functions and lack of operational nexus among the operational tactical and strategic levels. Such failures are overcome by adaptations on internal communications of internal codes among the institution different directional levels and, by the informal communications. The results indicate that the institution has a strategic planning, but it does not represent the will of the police community; the internal functioning has structural, financial, personnel processes communication that reflect on the delivery of services, ostensive presence of police in uniform; the use of resources is centralized in the state capital and they are insufficient, especially the troops, training, fuel; the resources are not distributed systematically and, the lower ranks (regional police Regional Police Departments, Battalions, Independent Police Departments, Platoons) seek through informal relations with the Municipalities, private companies to meet the needs that minimize the difficulties. The study shows that the Military Police is subject to a strong political influence at all levels